LITERATURE ANALYSIS: EVALUATION OF THE IMPLEMENTATION OF THE VILLAGE FINANCIAL SYSTEM (SISKEUDES) ON VILLAGE FINANCIAL MANAGEMENT - Hervy Sakkinah; Nur Avni Syamsuddin; Luh Made Ekasari; Jamaluddin (RADJA PUBLIKA, 2025)
The implementation of the Village Financial System (SISKEUDES) has become a pivotal step in enhancing the efficiency, transparency, and accountability of village financial management in Indonesia. This study aims to analyze the impact of SISKEUDES implementation on financial management practices while identifying the technical and policy challenges that arise during its application. Employing a literature review approach, the research examines previous studies and recent publications focusing on efficiency, transparency, accountability, and operational constraints associated with the system. The findings indicate that SISKEUDES has significantly improved the overall quality of village financial management by promoting better reporting accuracy and timeliness. Nevertheless, technical issues such as system errors and data input difficulties continue to pose challenges that require sustained attention. The study underscores the importance of continuous evaluation and system improvement to optimize performance. This research contributes to a deeper understanding of the dynamics of local governance reform, emphasizing both the potential and limitations of SISKEUDES, and provides valuable insights for policymakers and stakeholders aiming to strengthen financial accountability at the village level.